Influence of Adding Nanoparticles of Silver Vanadate on Antibacterial Effect and Physicochemical Properties of Endodontic Sealers - Teixeira, Ana Beatriz Vilela; Vidal, Carla Larissa; Albiasetti, Tainara; Castro, Denise Tornavoi de; Reis, Andrea CÃ¢ndido dos (Iranian Endodontic Journal, 2019)
Introduction: The aim of this study was adding the nanostructured silver vanadate decorated with silver nanoparticles (AgVO3) (0, 2.5, 5, and 10%) to the endodontic sealers AH-Plus, Sealer 26 and Endomethasone N, and evaluate the antimicrobial activity, solubility and pH. Methods and Materials: The antimicrobial activity of freshly mixed sealers (n=10) and set sealers (n=9) against Enterococcus faecalis (E. faecalis) was evaluated by colony forming units per milliliter and epifluorescence microscopy. Solubility (n=9) and pH (n=10), 6 and 24 h and 7, 14, and 30 days were also evaluated. The Kruskal-Wallis and Dunn’s post-test were applied for the antimicrobial activity of fresh sealers. ANOVA and Tukey’s post-test was used for set sealers and solubility, and Friedman’s two-way analysis of variance for pH (α=0.05). Results: The fresh sealers inhibited E. faecalis. Set Sealer 26 (5 and 10% AgVO3) and Endomethasone N (2.5, 5, and 10% AgVO3) presented higher activity then the corresponding controls. Modification with AgVO3 did not influence the solubility of AH Plus and Sealer 26, but Endomethasone N (5%) presented reduced solubility. The AH-Plus groups showed acidic pH, and Sealer 26, basic pH after 30 days. Endomethasone N (5 and 10% AgVO3) presented statistical difference compared to 0% (P<0.05). Conclusion: In this in vitro study all fresh sealers and set Sealer 26 (5 and 10%) and Endomethasone N (2.5, 5, and 10%) presented higher antimicrobial activity than controls. The modification with 5% and 10% AgVO3 decreased solubility and pH of Endomethasone N, but did not affect the other groups. Keywords: Antimicrobial Activity; Endodontic Sealer; Nanoparticles; Silver Vanadate; Solubility